New Application in Technological Preparations for Investment Casting Production in Aircraft Industry - Sladek, Augustin; Pastircak, Richard; Bruna, Marek; Remisova, Anna (Manufacturing Technology Journal, 2017)
Nowadays, foundries do not sufficiently utilizes computer support during the creation of technical documentation. Instead of computer documentation, foundries are using classical method for designing technological documentation and the computer aid is only discrete. For the area of foudry technology, it is inappropriate to use conventional CAPP systems which use group technology because they work with a simple representative selection from the database according to the characteristics. The submitted article shows a solution for systems interconnection and the possibilities of using the simultaneous engineering for aircraft industry. A new system was designed serving as the creation tools for technological documentation, whose role is to effectively benefit from group technology with use of latest software capabilities.
Keywords: CAD; CAE CAPP; turbine